Handbook of economic growth - Aghion, Philippe, 1956-; Durlauf, Steven N., 1958- (Amsterdam ; Boston ; Heidelberg ; London ; New York ; Oxford ; Paris ; San Diego ; San Francisco ; Singapore ; Sydney ; Tokyo : Elsevier, 2005)
The Handbook of Economic Growth provides a broad review of the research topics, empirical findings, and methods that comprise modern growth economics. The chapters, written by research leaders, summarize and evaluate recent advances while explaining where further research might be profitable. With analyses that are provocative and controversial because they are so directly relevant to public policy and private decision-making, this volume upholds the standard for excellence in applied economics set by Volumes 1A and 1B (2005).
Rozsáhlý čtyřsvazkový sborník přináší ucelený přehled moderní teorie ekonomického růstu. Přední odborníci zde shrnují hlavní výzkumné směry, empirické poznatky i metodologické přístupy, které formují současné pojetí růstové ekonomie. Publikace nabízí kritické zhodnocení dosavadního vývoje oboru i náměty pro další bádání, přičemž zdůrazňuje praktickou relevanci analýz pro hospodářskou politiku a strategické rozhodování.
Volume 1A. 2005. xxviii, 1059, I-46 stran — Volume 1B. 2005. xxv, 1821 stran — Volume 2A. 2014. xiv, 513, I-35 stran — Volume 2B. xiv, 515-1069, I-35 stran. 2014
Obsahuje bibliografické odkazy a rejstříky
Keywords: ekonomický růst; teorie růstu; sborníky; economic development; theory of economic growth